2010
DOI: 10.1007/bf03324816
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and its association with disability and comorbidity in a community-dwelling sample of seniors in Montreal: a cross-sectional study

Abstract: Findings on the relationship between frailty and sociodemographic variables, morbidity and disability, support previous studies, providing further evidence that although frailty seems to be a distinct geriatric concept, it also overlaps with other concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 23 publications
7
100
0
5
Order By: Relevance
“…It is very important for our clinical practice that frailty is independently predictive of fall incidents, comorbidities, worsening of mobility or activities of daily life, hospitalization, and death (Fairhal et al 2008;Wong et al 2010;Heuberger 2011;Jürschik et al 2012;Runzer-Colmenares et al 2014). At the end of our study, as many as 39.2 and 43.3 % of the older adult participants were found frail and pre-frail, respectively.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is very important for our clinical practice that frailty is independently predictive of fall incidents, comorbidities, worsening of mobility or activities of daily life, hospitalization, and death (Fairhal et al 2008;Wong et al 2010;Heuberger 2011;Jürschik et al 2012;Runzer-Colmenares et al 2014). At the end of our study, as many as 39.2 and 43.3 % of the older adult participants were found frail and pre-frail, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…It is very important for our clinical practice that this frailty phenotype is independently predictive (over 3 years) of falls, worsening of mobility or activities of daily life, disability, hospitalization, and death. Additionally, some previous research results point out the association of frailty with comorbidity (Wong et al 2010;Heuberger 2011;Jürschik et al 2012). However, this association has not been considered adequately in the literature probably because the pathogenesis has not been fully discerned.…”
Section: Introductionmentioning
confidence: 99%
“…The Cardiovascular Health Study (CHS) index developed by Fried et al (2001) is an operational definition of frailty in older subjects based on the presence of any three of the following five characteristics: shrinking, weakness, poor endurance, slowness, and low physical activity. While other population-based studies confirmed original findings from the CHS of the overlaps and dissociations among frailty, disability, and comorbidity, there were important differences in the reported prevalence estimates (from 6.9% to 20.0%; Fried et al 2001;Woods et al 2005;Ottenbacher et al 2005;Bandeen-Roche et al 2006;Cesari et al 2006;Gill et al 2006;Hirsch et al 2006;Avila-Funes et al 2008;Santos-Eggimann et al 2009;Wong et al 2010).…”
Section: Introductionmentioning
confidence: 67%
“…The prevalence estimate of frailty syndrome The Italian Longitudinal Study on Aging, 2nd survey, 1995Aging, 2nd survey, -1996Aging, 2nd survey, and 3rd survey, 2000Aging, 2nd survey, -2001 ADL Activities of Daily Living, HR hazard ratios, CI confidence interval, IADL Instrumental Activities of Daily Living a HRs were adjusted for age, sex (coded 0 for women and 1 for men), and failure type as covariate in partially adjusted models b HRs were adjusted for age categories (coded 1 for 65-69, coded 2 for 70-74, coded 3 for 75-79, and coded 4 for 80-84), gender (coded 0 for women and 1 for men), education, pack-years {pack-years cigarettes [coded 0 for pack-years cigarettes = 0 (never smoking) and 1 for pack-years cigarettes ≥0.5]}, Instrumental Activities of Daily Living score, Mini Mental State Examination score, Charlson comorbidity index, serum albumin levels, in fully adjusted models for the nondemented population; MMSE and IADL scores were excluded from the models for the demented population in the ILSA was also similar to that of another Italian population-based study, the Invecchiare in Chianti Study (8.8%; Cesari et al 2006). However, several other population-based studies have applied the same definition of frailty syndrome of the CHS and the ILSA with very different prevalence estimates that varied from 6.9% to 20.0% (Fried et al 2001;Woods et al 2005;Ottenbacher et al 2005;Bandeen-Roche et al 2006;Gill et al 2006;Hirsch et al 2006;AvilaFunes et al 2008;Wong et al 2010). In these population-based studies, differences in the tools used in estimating the different components of the frailty syndrome, different races, and different age and gender distribution of the samples could be the source of this great variability.…”
Section: Discussionmentioning
confidence: 91%
“…Frailty considerably changes care utilisation pattern due to a significant increase in risks of comorbidity [40]- [42] and adverse outcomes, such as fall, post-operative complications, disability, mortality, prolonged length-of-stay, readmission and institutionalisation. Therefore, there is a considerable benefit in identifying these patients and proactively planning their care to enable rapid control of symptoms and prioritisation of anticipated needs.…”
Section: Frailtymentioning
confidence: 99%